The Portrayal of Gender in Health Care: An Examination of Hospital Photographic Archives - Dansereau, François (Archivaria, 2020)
Through records creation practices, nation-states, institutions, and corporations impose or attempt to instill particular world views according to their interests, activities, and desires. Health care organizations are no different. This article examines photographic archives available at the recently formed McGill University Health Centre (MUHC) Archives and Special Collections. It explores the image institutional records creators conveyed through the production and dissemination of photographs depicting doctors, nurses, other health care professionals, and volunteers. The article discusses the dynamics of power at play in institutional photographs and uses a gendered frame of reference to confront the power of institutional authorities in their capacity as creators of records and records-creation frameworks. It uses this perspective to evaluate the scope of the archival photographic collection at the MUHC Archives and Special Collections and to conceive subsequent ensuing archival interventions. The article uses critical visual literacy and deconstructionist approaches, highlighting different archival paradigms that will activate the archival collection and help construct an archival environment that will enable counter-narratives. RÉSUMÉ Les entités nationales, institutionnelles et corporatives imposent ou tentent d’imposer, à travers la production de documents, leur vision selon leurs intérêts, activités et désirs. Les institutions médicales ne font pas exception. Cet article effectue l’analyse de photographies d’archives se trouvant au nouveau programme d’archives du Centre universitaire de santé McGill (CUSM). Il examine l’image visuelle que les créateurs de documents ont forgée à travers la production et la diffusion de photographies de médecins, infirmières, membres des autres professions du domaine de la santé et bénévoles. Cet article se penche sur les dynamiques de pouvoir mises en évidence à travers des photographies institutionnelles et propose un cadre analytique du genre afin de confronter le pouvoir institutionnel associé à la production de documents. Cette approche est mise de l’avant afin d’évaluer l’étendue de la collection d’archives au Service des archives et collections spéciales du CUSM et pour concevoir les interventions archivistiques qui suivent. Cet article utilise une approche de littératie visuelle critique et de déconstruction des archives, soulignant différents paradigmes archivistiques qui vont mener vers l’activation de la collection d’archives et la formation d’un environnement archivistique rendant possible l’élaboration de contre-narratifs.